Constitutional dilemmas in the Hungarian regulation of euthanasia - Vadál, Ildikó; Szappanyos, Melinda (POLARITIES, 2024)
The aim of the present paper is to compare the pieces of Hungarian law on euthanasia to the Fundamental Law of Hungary. Surely, the topic is widespread, therefore the present research will be continued, bringing in new perspectives. In this paper, the regulation of euthanasia will be reviewed from a constitutional law point of view. We attempt to analyse whether the legislation on the decisions about ending our lives ensures the respect for the fundamental rights incorporated in the Fundamental Law of Hungary. Special attention will be paid to the right to human dignity, the right to self-determination, the prohibition of discrimination, the probihition of torture, inhuman or degrading treatment or punishment, and the right to privacy. The intention behind the present paper is not simply providing critical analysis of the legislation in force, but working out and recommending amendments, which put human life into the focus of the legislation, meanwhile being in harmony with the Fundamental Law of Hungary.